Feasibility Study of Converting an isolated 5 MW Fuel-Oil Power Plant in the Dominican Republic into a PV-Fuel-Oil Hybrid System - Jannik Thomsen (2019)
This research studies the feasibility of designing a hybrid system by combining existing generators with a photovoltaic power plant and a battery bank. The investigation of a possible conversion of a 5 MW fuel oil driven stand-alone power plant in the Dominican Republic to a photovoltaic fuel-oil hybrid system is based on simulations with different programs. To get a detailed and realistic image of the feasibility the regional conditions and the components of the hybrid system are discussed. The most significant results are given by the software HOMER Pro containing the dimension of the components for the most economical application. Hybrid systems in the remote areas in the Dominican Republic are expected to promise a high degree of success since the cost of energy can be decreased significantly by including renewable sources into conventional systems. Due to very well suiting conditions in this region especially PV-arrays can generate a lot of energy. The intention of the study is, that it serves as an example for the electrification of rural areas in the Caribbean and around the world